Differential modulation of inflammatory cytokines by recombinant IL-10 in IL-1β and TNF-α ̶ stimulated equine chondrocytes and synoviocytes: impact of washing and timing on cytokine responses - Hoda A. Elkhenany; Renata L. Linardi; Kyla F. Ortved (BMC Veterinary Research)
Abstract Osteoarthritis (OA) remains a challenging joint disorder necessitating effective anti-inflammatory interventions. In this study, our primary objective was to establish an in vitro protocol that replicates the clinical investigation of anti-inflammatory drugs intended for OA management. Focusing on recombinant IL-10 (r.IL-10) as a potential anti-inflammatory treatment, we designed and implemented two distinct protocols to evaluate the efficacy of r.IL-10 in modulating chondrocyte and synoviocyte inflammation. The experimental design involved sequential stimulation with IL-1β and TNF-α for 24 h, followed by washing (model 1) or not washing (model 2) the cells before r.IL-10 treatment. Samples were collected after 6–24 h of treatment. Cellular responses were evaluated by quantifying gene expression and synthesis of key inflammatory cytokines and proteases. The expression and synthesis of inflammatory cytokines and proteases was significantly affected by washing and treatment time. The expression of IL-1β, TNF-α, IL-8, MMP-13, and ADAMTS5 were effectively reduced in r.IL-10-treated chondrocytes and synoviocytes in model 2 after 24 h, particularly at concentrations of 10 and 20 ng/mL. r.IL-10 treatment significantly increased IL-6 gene expression in chondrocytes at all time points. However, in synoviocytes, IL-6 expression was significantly lower in model 2 after 24 h of r.IL-10 treatment. r.IL-10 treatment significantly decreased IL-1β and TNF-α content in synoviocyte supernatants, particularly in model 2 at concentrations of 10 and 20 ng/mL after 6 and 24 h. r.IL-10 treatment in chondrocytes led to a significant decrease in IL-1β supernatant concentrations in model 2 after 24 h only. This study demonstrated that r.IL-10 treatment effectively reduces key inflammatory markers and matrix metalloproteinase activity in both chondrocytes and synoviocytes, particularly in model 2 where cells were not washed prior to treatment. These findings highlight r.IL-10’s potential as a robust anti-inflammatory agent for OA management and suggest its critical role in developing effective therapeutic strategies for OA.